Two questions from philosophy to economics - Rodriguez-Cardenas, Frank E. (2023)
This paper is focused on the area of philosophy of economics and tries to analyze two problems of economics from its philosophical categories. The first problem is: what are the errors or shortcomings that economics goes through in its work as a science, and the second raises the problem of whether there is the possibility of a strengthening between economics and ethics in order to have an efficient economic activity and moral systems (or perhaps one). The objective of this work is a review of the theoretical bases, principles, assumptions, methodology and ways of proceeding of the scientist in his work and proceeding within economics. The present research work is framed within the documented or bibliographic research, the theoretical approach, therefore, will be that of discourse analysis to carry out a philosophical discursivity in the ontological, axiological, epistemic and ethical aspects. The conclusion to be drawn from the two questions posed to economics by philosophy would be, with respect to the first, the conceptual and methodological errors made by economists or schools, from the principles and economic theories, have contributed to certain gaps and collapses in their work and acts of prediction, as well as their moral stance and their theorization. And with respect to the second problem, the answer is yes, because, having better ways of reconstruction and theoretical strengthening of the economy hand in hand with ethics, could strengthen and improve personal relationships along with the way of living in the path of quality of life and development of any human society.